Endothelial dysfunction in cardiac microvascular endothelial cells : an investigation into cellular mechanisms and putative role of oleanolic acid in reversing endothelial dysfunction - Mudau, Mashudu (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScMedSc (Biomedical Sciences. Medical Physiology))--University of Stellenbosch, 2010.